The correlative triad among aging, dopamine, and cognition: Current status and future prospects - Bäckman, Lars; Nyberg, Lars; Lindenberger, Ulman; Li, Shu-Chen; Farde, Lars (Neuroscience and biobehavioral reviews, 2006)
The brain neuronal systems defined by the neurotransmitter dopamine (DA) have since long a recognized role in the regulation of motor functions. More recently, converging evidence from patient studies, animal research, pharmacological intervention, and molecular genetics indicates that DA is critically implicated also in higher-order cognitive functioning. Many cognitive functions and multiple markers of striatal and extrastriatal DA systems decline across adulthood and aging. Research examining the correlative triad among adult age, DA, and cognition has found strong support for the view that age-related DA losses are associated with age-related cognitive deficits. Future research strategies for examining the DA-cognitive aging link include assessing (a) the generality/specificity of the effects; (b) the relationship between neuromodulation and functional brain activation; and (c) the release of DA during actual task performance.